Naturally occurring coumestans from plants, their biological activities and therapeutic effects on human diseases. (July 2021) - Tu, Yanbei; Yang, Ying; Li, Yanfang; He, Chengwei
Abstract: Naturally occurring coumestans are known as a collection of plant-derived polycyclic aromatic secondary metabolites which are characterized by the presence of an oxygen heterocyclic four-ring system comprising a coumarin moiety and a benzofuran moiety sharing a C˭C bond. Recently, there is an increasing attention in excavating the medicinal potential of coumestans, particularly coumestrol, wedelolactone, psoralidin and glycyrol, in a variety of diseases. This review is a comprehensive inventory of the chemical structures of coumestans isolated from various plant sources during the period of 1956–2020, together with their reported biological activities. 120 molecules were collected and further classified as coumestans containing core skeleton, dimethylpyranocoumestans, furanocoumestans, O-glycosylated coumestans and others, which showed a wide range of pharmacological activities including estrogenic, anti-cancer, anti-inflammatory, anti-osteoporotic, organ protective, neuroprotective, anti-diabetic and anti-obesity, antimicrobial, immunosuppressive, antioxidant and skin-protective activities. Furthermore, this review focuses on the counteraction of coumestans against bone diseases and organ damages, and the involved molecular mechanisms, which could provide important information to better understand the medicinal values of these compounds. This review is intended to be instructive for the rational design and development of less toxic and more effective drugs with a coumestan scaffold. Graphical Abstract: ga1 Highlights: 120 natural coumestans and their various biological activities are covered in the comprehensive review. The structure classification of natural coumestans is provided for the first time. Counteraction of coumestans against bone diseases and organ damages is highlighted. The collected results highlight the potential development of novel drugs with a coumestan scaffold.